1982
DOI: 10.1111/j.1365-2362.1982.tb00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor binding increased by high carbohydrate low fat diet in non‐insulin‐dependent diabetics

Abstract: In comparison to a traditional low carbohydrate diet (LC), the effect of an isocaloric high carbohydrate, high fibre diet (HC) upon the insulin binding to mononuclear blood cells of seven non-insulin-dependent diabetics was examined. Each subject, in random order, took both diets for 6 weeks each. There was no significant difference in weight during either dietary period, but a significant (P less than 0.05) increase in the monocyte insulin binding activity on the HD diet (tracer specific binding: 4.2% HC; 3.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In a crossover study using low (control) and high carbohydrate diets, Ward et al (1982) found greater monocyte insulin receptor binding after the high carbohydrate diet compared with the control period. Hjollund et al carried out intravenous insulin tolerance tests in people with T2DM and found that in vivo insulin action (expressed as a rate constant for plasma glucose disappearance) had increased in the group receiving a low-fat, high-starch, highfibre diet compared with baseline, while no change had occurred in the control group.…”
Section: Short-and Medium-term Dietary Intervention Studiesmentioning
confidence: 99%
“…In a crossover study using low (control) and high carbohydrate diets, Ward et al (1982) found greater monocyte insulin receptor binding after the high carbohydrate diet compared with the control period. Hjollund et al carried out intravenous insulin tolerance tests in people with T2DM and found that in vivo insulin action (expressed as a rate constant for plasma glucose disappearance) had increased in the group receiving a low-fat, high-starch, highfibre diet compared with baseline, while no change had occurred in the control group.…”
Section: Short-and Medium-term Dietary Intervention Studiesmentioning
confidence: 99%
“…These acute effects cannot be ascribed to increased insulin sensitivity but may be due to the slowed rate of intestinal transit and an attenuated stimulus; however, the observation in some studies that chronic ingestion of fiber is associated with lower basal glucose levels and decreased urinary excretion of C-peptide (60,61) suggest an increase in insulin sensitivity or a decreased demand for insulin. Indeed, in the studies where this has been examined (62)(63)(64), an increase in insulin binding to monocyte receptors for insulin has been found. This effect may clearly have some importance in the obese patient.…”
Section: Physiologic Effects Of Fibermentioning
confidence: 99%
“…1980). This may be related to the prior dietary therapy of the diabetics in our study, which included caloric restriction and high carbohydrate/high fibre content (55% carbohydrate), both shown to ameliorate the binding defect in diabetes (Beck-Neilsen, 1980;Ward, 1982). When all the subject groups had been on standardized LC diets (40% carbohydrate) for 6 d, the diabetics showed lower insulin binding ( Table 1).…”
Section: Discussionmentioning
confidence: 82%